THE INFLUENCE OF MOTIVATION, KNOWLEDGE, AND SKILLS ON EMPLOYEE WORK SAFETY IN THE FIBER LINE UNIT AT PT. RIAU ANDALAN PULP AND PAPER PANGKALAN KERINCI - Sinaga, Sri Lestari; Munthe, Novita Br Ginting; Aritonang, Barita; Sinaga, Evi Yuni Sintia (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Occupational Safety and Health (OSH) is an important aspect in the world of work that aims to protect workers from accidents and occupational diseases. This study aims to determine the effect of motivation, knowledge, and skills on employee safety at PT. Riau Andalan Pulp and Paper Pangkalan Kerinci. The method used is quantitative descriptive with analysis of variance (ANOVA) and a sample of 64 respondents. The results show that motivation, knowledge, and skills have a significant effect on occupational safety. Knowledge has the most dominant influence. These findings indicate that improving knowledge and skills through training can strengthen the safety culture. The conclusion of this study is that motivation, knowledge, and skills have a positive and significant effect on improving occupational safety. Therefore, companies need to develop OSH training and socialization programs and create a work environment that supports compliance with safety procedures. Thus, companies can improve occupational safety and reduce the risk of accidents and occupational diseases. This research contributes to the development of effective occupational safety strategies in companies.